The Role of Plain Language Summaries in the Context of Knowledge Sharing: A Systematic Literature Review - Siti Alyza Rizqika Noordin; Muhamad Prabu Wibowo; Tamara Adriani Salim (Universitas Negeri Padang, 2026)
Plain Language Summaries (PLS) are used to increase the readability and public accessibility of research findings, making them highly relevant within knowledge sharing (KS) practices. This study conducted a Systematic Literature Review (SLR) using the Scopus database to identify the roles of PLS in KS and the technologies utilized in their creation. Article selection followed the PRISMA framework, resulting in 24 eligible studies. Data were extracted and synthesized using Microsoft Excel. The findings indicate that PLS play a critical role in simplifying scientific information, enhancing comprehension, expanding dissemination reach, and strengthening user engagement. Additionally, eight categories of technologies were identified, including readability tools, machine learning, large language models, knowledge translation platforms, and multimedia production tools. Overall, PLS serve as a strategic instrument for cross-audience knowledge transfer and require strengthened standards and governance of technological tools to ensure their quality and effectiveness.